VATA (FICUS BENGHALENSIS) A DETAILED REVIEW FROM CLASSICAL TEXTS - Nirmal Narayanan; Usha Patil (International Journal of Ayurveda and Pharma Research, 2019)
Nature is enriched with a huge variety of plant life having distinctive properties. Human ardor for herbal medicine dates lower back to Vedic length. People have been making use of plant materials lengthy earlier than scientific explanations were advanced. One of the tremendous capabilities of the local health practice is they use domestically available and quite often readily available sources. The “Birds eye view” of our great saints led to the invention of different medicinal plants one among them is drug Vata. Vata is considered as one among the Pancha valkala which constitute the famous Ksheeri vrukshas. Elaborate description of the plant Vata and its therapeutic action are explained by our Acharyas in Vedas, Puranas, and Samhithas and in the later Nighantus. Vata (Ficus bengalensis) is such a drug which is widely and cheaply available and is having many mentioning in the classics for its effectiveness in many diseases. Vata does not have any controversies in any of the literatures or classics regarding its identification or usage. The current article is to highlight the importance of drug Vata (Ficus benghalensis) and references has been collected from Vedas, Puranas, Samhita kala, Nighantu kala. Synonyms, Gana Varga, Vernacular names etc has been collected and arranged systematically.